Encouraging reading among children in care: the Edinburgh Reading Champion project - Colm Linnane (Scottish Journal of Residential Child Care)
The Edinburgh Reading Champion project is an innovative partnership project between two sections of City of Edinburgh Council: the Children and Families Department and Services for Communities. The project, funded by the Paul Hamlyn Foundation, seeks to improve access to books, libraries and reading activities for young people in residential care in Edinburgh.